Study of the Comparative Depression Indications to Students of the Physical Education in Al- Mustansiriyah University - Abdul Wahid, Amira; Abdul Matar, Shaima (Journal of Physical Education, 2015)
The research has five sections: - the first section is including introduction, the importance, problems, aims, hypothesis and fields if the research. The depression is considered as the most common mental disorders and more emotional problems, that pushing people to ask for psychological and social assistance. The depression is considered as a common disease cold to the psychologists as it the most prevalent, and is also called age illness or disease of civilization. The objectives of the research were:- 1. Identify the level of depressive symptoms among students of the physical education collage in al- Mustansiriyah university. 2. Identify differences in symptoms of depression among students according to gender. While the research hypotheses included:- 1. There are statistically significant differences in the level of depressive symptoms among students of the physical education collage. 2. There are statistically significant differences in symptoms of depression among students according to gender. Research procedures:- Select a sample of (85) students from the students of the physical education collage, females (43) , males (42). For the purpose of achieving the goals of current research, the researcher using the depression scale, which is distributed on four areas, symptoms include (mood, cognitive, behavioral and physical). Conclusions:- After analyzing the results of research and discussion , it was reached some conclusions:- 1. Existence of a statistically significant difference in the average sample of students in the physical education collage on a scale of depression symptoms. 2. Existence of a statistically significant difference between the average of males and females in favor of females with symptoms of depression. Recommendations:- Finally I recommend a number of recommendations:- 1. Preparation programs and entertaining trips for college students for the purpose of consolidating them in the society. 2. Developing guidance programs to reduce the symptoms of depression for the college students. 3. Make a comparative study between depression and concentration on self